The new public service transnationals: consequences for labour. (1st October 2008) - Judith Clifton; Daniel Díaz-Fuentes
Abstract : Since the late twentieth century, a significant number of public service providers operating in networks, previously defined as nationally-bound entities largely owned and controlled by the state, have embarked on aggressive expansion strategies abroad. This transnationalisation was a consequence of 1970s organisational reform, particularly privatisation, sectoral liberalisation and the liberalisation of Foreign Direct Investment. This article examines the recent organisational transformations of public service providers, particularly those based in the European Union, that have been at the forefront of this development, with a particular focus on electricity, telecommunications and postal services. Public service provider transformation, including transnationalisation, has significant consequences for work inside these organisations.